Specificities of transplantation of kidneys procured from donors with situs inversus totalis – A case report and review of the literature - Petrovic, Milica; Rabrenović, Violeta; Stamenković, Dušica; Vavić, Neven; Kovačević, Zoran; Ignjatović, Ljiljana; Jovanović, Dragan; Antić, Svetlana; Milović, Novak; Tomić, Aleksandrar; Bančević, Vladimir (Vojnosanitetski pregled, 2014)
Introduction. Situs inversus totalis (SIT) represents a total vertical transposition of the thoracic and abdominal organs which are arranged in a mirror image reversal of the normal positioning 1. We presented a successful pre-dialysis kidney transplantation from a living sibling donor with SIT and the longest donor follow-up period, along with analysis of the reviewed literature. Case report. The pair for pre-dialysis kidney transplantation included a 68-year-old mother and 34-year-old daughter at low immunological risk. Comorbidities evidenced in kidney donors with previously diagnosed SIT, included moderate arterial hypertension and borderline blood glucose level. Explantation of the left donor kidney and its placement into the right iliac fossa of the recipient were performed in the course of the surgical procedure. A month after nephrectomy, second degree renal failure was noticed in the donor. A 20-month follow-up of the donor’s kidney and graft in the recipient proved that their functions were excellent. Conclusion. In donors with previously diagnosed SIT the multidisciplinary approach, preoperative evaluation of the patient and detection of possible vascular anomalies are required to provide maximum safety for the donor.
Keywords: situs inversus; kidney transplantation; tissue donors